Polyphenols from cagaita (Eugenia dysenterica DC.) and cambuci (Campomanesia phaea Berg.): bioactivities in diet-induced obesity and their metabolic alterations - Donado-Pestana, Carlos Mario (2016)
Obesity and overweight have reached epidemic proportions and their prevalence has increased dramatically in the last decades worldwide. This has resulted in a dramatic increase in the incidence of obesity-associated metabolic alterations including type 2 diabetes, cardiovascular complications, and certain types of cancer. Evidences suggest that bioactive compounds present in fruit and vegetables, including polyphenols (or phenolic compounds), may exert beneficial effects against the development of obesity and associated alterations. Brazil is the world\'s third largest fruit producer and the seventh largest producer of tropical fresh fruits; however, only a few of them are being exploited commercially, perhaps due to the limited amount of information available about their chemical composition, and biochemical, nutritional and functional properties. Cagaita (Eugenia dysenterica DC.) and cambuci (Campomanesia phaea Berg.) are fruit species of the Myrtaceae family growing in the regions of the Brazilian Cerrado and Atlantic Coastal Forest biomes, respectively. Cagaita and cambuci fruits are used in various typical preparations, mainly jams, jellies, ice-cream, and liqueurs; whereas both fruit and leaves are used as popular alternative medicine by local communities to treat various disturbs such as diarrhea, diabetes, and jaundice. Previous studies have demonstrated the antioxidant and antidiabetic potential from cagaita and cambuci polyphenols in in vitro assays. Thus, in the present study, we investigated whether the administration of polyphenol-rich extracts from cagaita and cambuci, at two different doses, protect mice from diet-induced obesity and associated alterations. Two biological models, preventive and therapeutic, were designed for cagaita, and preventive for cambuci. For the preventive protocols, C57BL/6J mice fed either with a chow or a high-fat, high-sucrose (HFHS) diets were daily treated by gavage with water or polyphenols-rich extracts at two doses for 8 weeks. The findings demonstrate that polyphenols from cagaita prevented body weight and fat mass gains, attenuated fasting hyperglycemia and dyslipidemia, and reduced hepatic lipid accumulation. On the other hand, polyphenols from cambuci showed absence of changes in body weight and adiposity; however, an attenuation of adipose tissue inflammation was observed for both doses tested. Additionally, polyphenols from cambuci were effective in ameliorating glucose tolerance, as well as reducing fasting hyperglycemia, and improving dyslipidemia. For the therapeutic protocol, C57BL/6J obese mice induced by the intake of a HFHS diet for six weeks were treated with polyphenols from cagaita at two doses by oral gavage for further 8 weeks. Polyphenols from cagaita improved glucose homeostasis and attenuated dyslipidemia in obese mice, without affecting body weight and adiposity. Mechanistically, these beneficial actions seem to be mediated, at least in part, through a reduction in hepatic inflammation. In conclusion, polyphenols from cagaita and cambuci have a potential protective role in diet-induced obesity and their metabolic alterations.